2018
DOI: 10.1016/j.nedt.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

‘Doing it for real now’ – The transition from healthcare assistant to newly qualified nurse: A qualitative study

Abstract: Van Gennep's Rites de Passage and Bridge's work on organisational change were combined to theoretically analyse participants' accounts of transition. This illustrated that transition is not always linear with clearly defined and bounded stages but can also be seen as a more undulating or organic process with curving, slanting and overlapping phases. NQNs can therefore simultaneously occupy more than once phase in their journey of transition. Implications for students, higher education and practice are highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Participants were able to take what they observed and learned in their work as CNAs, thus construct and transfer from their previous experiences, and develop new ways of thinking and processing information. Consistent with Draper, participants with a background as CNAs felt able to challenge and question more as they prepared for their new roles.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Participants were able to take what they observed and learned in their work as CNAs, thus construct and transfer from their previous experiences, and develop new ways of thinking and processing information. Consistent with Draper, participants with a background as CNAs felt able to challenge and question more as they prepared for their new roles.…”
Section: Discussionmentioning
confidence: 88%
“…This may be related to variations of acculturation into a program and/or the manner in which clinical experiences are supervised and how boundaries are established in nursing programs in the U.S. According to Draper, the transition to a student role was sometimes complicated by working as a CNA. As seen in this study, shifting from working as a CNA to being a nursing student was difficult at times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have demonstrated that expectations differ between NGRNs, senior nurses and preceptor/nurse educators (El Haddad, Moxham, & Broadbent, 2017;Lea & Cruickshank, 2015;Missen et al, 2016a) with NUMs often having the unrealistic expectation of NGRNs entering the workforce as experts (El Haddad et al, 2017). There are also higher expectations placed on NGRNs who have worked in nursing assistant roles during their undergraduate course and as such there was a reported inconsistency in the preceptorship provided to these nurses now in the registered nurse role (Draper, 2018;Law & Chan, 2016).…”
Section: Expectations and Readinessmentioning
confidence: 99%
“…New graduate registered nurse (NGRN) transition has been the focus of research in recent years (Ankers, Barton, & Parry, 2018;Blevins, 2018;Draper, 2018;Missen, McKenna, Beauchamp, & Larkins, 2016;Missen, McKenna, Beauchamp, & Larkins, 2016;Ortiz, 2016), succeeding Kramer's seminal 1974 Shock. New graduate nurses transitioning from student to registered nurse face many challenges in practice however the provision of safe and efficient care of their patients is paramount (Duchscher, 2008(Duchscher, , 2009Myers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%